The impact of VC backing on the corporate governance of Chinese IPOs. Issue 3 (7th August 2017) - Wang, Qing (Sophie); Anderson, Hamish D.; Chi, Jing
Abstract : Purpose: The purpose of this paper is to investigate how venture capital (VC) backing influences the board size and independence and how VC backing and board structure impact firm performance in China. Design/methodology/approach: Using hand-collected data from 924 initial public offering (IPO) prospectuses covering the period from January 2004 to December 2012, the authors investigate the impact of VC backing on board size, board independence and firm market performance through regression analysis. A two-stage approach is also used to address the endogeneity issue. Findings: The authors find robust evidence that VC-backed IPOs have more independent boards, after controlling for CEO and firm characteristics, and the potential endogeneity concerns. Furthermore, firms backed by VCs with management political ties (PTs) have more independent directors with industry relevant expertise than other firms. While no significant relationship is found between board independence and firm performance, the authors present some evidence that IPOs which have a larger percentage of independent directors with industry relevant expertise exhibit higher long-term stock returns, and VCs with management PTs also improve IPO long-run stock performance. Research limitations/implications: Although VC is new in China and the Chinese capital market has relative poor corporate governance and weak minority shareholder protection, the authors find support in this paper that VC backing is valuable to IPO firms in China not only through providing funding but also by providing political ties and industry experience. However, Chinese regulatory and institutional settings have strong impact on test results and they change rapidly, so the results may not apply to other period in Chinese markets. Originality/value: This paper sheds lights on the influences of VC backing on corporate governance and firm performance in a transitional and emerging economy. It discovers the value of VC investors in a transitional economy as of providing political ties and industry experience. The new definition of independent directors suggested bySuchard (2009) is first used by our paper in the Chinese context.